Engagement in community music classes sparks neuroplasticity and language development in children from disadvantaged backgrounds - Kraus, Nina; Hornickel, Jane; Strait, Dana L.; Slater, Jessica; Thompson, Elaine (Frontiers in Psychology, 2014)
Children from disadvantaged backgrounds often face impoverished auditory environments, such as greater exposure to ambient noise and fewer opportunities to participate in complex language interactions during development. These circumstances increase their risk for academic failure and dropout. Given the academic and neural benefits associated with musicianship, music training may be one method for providing auditory enrichment to children from disadvantaged backgrounds. We followed a group of disadvantaged primary-school students from gang reduction zones in Los Angeles, CA for two years as they participated in the Harmony Project. By providing free community music instruction for disadvantaged children, the Harmony Project promotes the healthy development of children as learners, the development of children as ambassadors of peace and understanding, and the development of stronger communities. Children who were more engaged in the music program—as defined by better attendance and classroom participation—developed stronger brain encoding of speech after two years than their less-engaged peers in the program. Additionally, children who were more engaged in the program showed increases in reading scores, while those less engaged did not show improvements. The neural gains accompanying music engagement were seen in the very measures of neural speech processing that are weaker in children from disadvantaged backgrounds. Our results suggest that community music programs such as Harmony Project provide a form of auditory enrichment that counteracts some of the biological adversities of growing up in poverty, and can further support for community-based interventions aimed at improving child health and wellness.